2021
DOI: 10.1021/acs.energyfuels.1c03348
|View full text |Cite
|
Sign up to set email alerts
|

Physical Insights about Viscosity Differences of Asphaltene Dissolved in Benzene and Xylene Isomers: Theoretical–Experimental Approaches

Abstract: This study characterized the rheological behavior of asphaltenes dissolved in aromatic solvents of different chemical nature to understand the solvent effect. For this purpose, n-C7 asphaltenes were obtained from extra-heavy crude oil and dissolved at three concentrations (1, 8, and 15 wt %) in solvents with different molecular structures: benzene and three xylene isomers. The experimental results revealed appreciable differences in the viscosity of the asphaltene solutions in each solvent which were more mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…There is a substantial lack of studies in the literature regarding both approaches, especially compared to experimental studies, which, in some cases, cannot be generalized beyond the samples investigated . Molecular dynamics (MD) simulations are a deterministic tool that can be used to derive physical insights regarding the relationship between macroscopic behaviors and structural and compositional characteristics. , Chen et al developed an MD model using reactive force fields (REAX-FF) to describe char oxidation processes in air, CO 2 , and O 2 –CO 2 atmospheres. The authors found that the O radical and CO 2 could adsorb and destroy the edge of representative PAH molecules in the char model during char oxidation and gasification.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial lack of studies in the literature regarding both approaches, especially compared to experimental studies, which, in some cases, cannot be generalized beyond the samples investigated . Molecular dynamics (MD) simulations are a deterministic tool that can be used to derive physical insights regarding the relationship between macroscopic behaviors and structural and compositional characteristics. , Chen et al developed an MD model using reactive force fields (REAX-FF) to describe char oxidation processes in air, CO 2 , and O 2 –CO 2 atmospheres. The authors found that the O radical and CO 2 could adsorb and destroy the edge of representative PAH molecules in the char model during char oxidation and gasification.…”
Section: Introductionmentioning
confidence: 99%
“…This is related to the synergetic interaction between the asphaltene molecules and the solvent, which was reported in the literature evaluating the aggregation and rheological behavior of asphaltenes dissolved in benzene and xylene isomers. 62 These results indicate that a multistructural description of asphaltenes not only allows for the data from the experimentally determined elemental analysis to be more adequately represented but also could be a suitable representation of the aggregation behavior. This is based on the fact that the aggregation states of the uniand multistructural approximation evaluated were different and considering that the multistructural representation describes the species determined experimentally by FTC-IR MS.…”
Section: Resultsmentioning
confidence: 84%
“…Despite their aggregation sizes being similar, their internal structures are substantially different, since maltene solvent contents resin and aromatics species that has a strong effect on the aggregation and rheological behavior of asphaltenes systems. This is related to the synergetic interaction between the asphaltene molecules and the solvent, which was reported in the literature evaluating the aggregation and rheological behavior of asphaltenes dissolved in benzene and xylene isomers . These results indicate that a multistructural description of asphaltenes not only allows for the data from the experimentally determined elemental analysis to be more adequately represented but also could be a suitable representation of the aggregation behavior.…”
Section: Resultsmentioning
confidence: 99%
“…9 In another paper, they characterized the rheological behavior of asphaltenes dissolved in benzene and xylene isomers to understand the solvent effect. 10 Hristova and Stoyanov reported that asphaltene precipitation starts and increases gradually rather than abruptly, and a new hypothesis was proposed to explain this difference with a conventional understanding of critical dilution. 11 Rogel et al investigated the fouling propensity of crude oil blends and found that the main driving force behind fouling seems to be related to the compatibility of the components.…”
Section: ■ Asphaltene Sciencementioning
confidence: 99%
“…In the first paper, they used petroleomics and molecular dynamics simulations to reconstruct a synthetic crude oil to understand the asphaltene aggregation behavior . In another paper, they characterized the rheological behavior of asphaltenes dissolved in benzene and xylene isomers to understand the solvent effect . Hristova and Stoyanov reported that asphaltene precipitation starts and increases gradually rather than abruptly, and a new hypothesis was proposed to explain this difference with a conventional understanding of critical dilution .…”
Section: Asphaltene Sciencementioning
confidence: 99%